Robust lubricious and low corrosive imidazolium hexafluorophosphate lubricant on multi-arc ion plating Ag-Cu/Ti film under sliding electrical contact. (November 2020) - Ding, Zhiqin; Wen, Xiaoqin; Qu, Rong; Fu, Yanlong; Yao, Ruiqing; Lu, Jinjun
Abstract: In the presence of flooded imidazolium hexafluorophosphate (LP108), Ag-Cu/Ti film prepared by multi-arc ion plating is well lubricated but severely corroded due to electrochemical corrosion even by using benzotriazole as a corrosion inhibitor. Although imidazolium methyltributylammomiumbis ((trifluoromethyl)sulfonyl)imide ([HEMIM]NTf2 ) is much less corrosive to Ag-Cu/Ti film, its lubricity is inferior to that of LP108. Preapplied LP108 on top of Ag-Cu/Ti film by dipping and withdrawing from 0.2 vol% LP108-ethanol solutions exhibits comparable lubricity as flooded LP108, and comparable corrosion as flooded [HEMIM]NTf2 . The localized liquid LP108 around spherical and top-flat droplets of Ag-Cu/Ti film gives birth to in-situ hybrid Ag-LP108 tribo-layer upon sliding contact. Meanwhile, tribochemical affinity between PF6 anion and tribo-surface is another reason for good lubricity. Highlights: Ag-Cu/Ti film is coated with imidazolium hexafluorophosphate by dipping and withdrawing from 0.2 vol.% solutions in ethanol. The distribution of LP108 is strongly affected by the surface topography of Ag-Cu/Ti film. Formation of a hybrid Ag-LP108 tribo-layer and good boundary property of LP108 allows sliding with low friction and wear. Low corrosion of preapplied LP108 to Ag-Cu/Ti film is observed.